Ruck-Play as performance indicator during the 2010 Six Nations Championship - A commentary - Gerrard, B. (International Journal of Sports Science and Coaching, 2014)
Analytics is the use of statistical analysis to support decision making in organisations. It is a growth area in many sectors including elite sport. Sports analytics is increasingly becoming part of the coaching toolkit as more and more teams analyse the numbers to go alongside their video analysis. Michael Lewis`s book, Moneyball: The Art of Winning an Unfair Game (2003), subsequently turned into an Oscar-nominated film starring Brad Pitt, tells the story of how the Oakland Athletics in Major League Baseball embraced the use of statistical analysis in player recruitment and has done much to publicise the possibilities of sports analytics as a David strategy for resource-constrained teams trying to become more competitive. Rugby union is one of the invasion team sports that has been more open than most to the possibilities for analytics as part of an evidence-based approach to coaching. As both a professor of business and sports analytics as well as a technical analyst with a leading English Premiership rugby union team, I welcome Kraak and Welman`s detailed study of ruck play using data from the 15 games in the 2010 Six Nations tournament. My comments on their study come mainly from the perspective of an active practitioner in elite sport. The main contribution of Kraak and Welman is the level of detail on ruck play, particularly the numbers of players involved in a ruck. The 15 games studied yielded 1,479 rucks all of which have been analysed. Although a mass of performance data on all aspects of the game is now available to teams from commercial providers, this data remains primarily tally data on the quantity of different activities and their outcomes, usually coded by player, time and field position. What we still lack is extensive data across teams and games on the micro technical detail of the activities. So, for example, teams are able to source data on the number of rucks contested and the outcomes but are less likely to have detailed data on the number of attackers and defenders involved in each ruck.